Masculinities, militarisation and the End Conscription campaign : War resistance in apartheid South Africa (Book collections on Project MUSE., 2017)
Masculinities, militarisation and the End Conscription Campaign explores the gendered dynamics of apartheid-era South Africa's militarisation and analyses the defiance of compulsory military service by individual white men, and the anti-apartheid activism of the white men and women in the End Conscription Campaign (ECC), the most significant white anti-apartheid movement to happen in South Africa. Military conscription and objection to it are conceptualised as gendered acts of citizenship and premised on and constitutive of masculinities. Conway draws upon a range of materials and disciplines t.